Coleridge’s Visions of 1816: the Political Unconscious and the Poetic Fragment - Fulford, Tim (Romanticism and Victorianism on the Net, 2012)
Taking as its point of departure the little-known fact that Coleridge was jailed as a Jacobin pro-French spy during his Scottish tour of 1803, this article explores the issue of the relationship of the fragmentary poems he published in 1816 to the political and personal contexts in which they had been composed years earlier. It speculates that what makes a Coleridgean fragment a fragment is what is left out—contextual material that the author could or would not admit into the published text because it configured divided loyalties, about which he was ashamed and guilty. Contributing to a debate about the ideological function of significant absences in Romantic poetry that Marjorie Levinson provoked by her discussion of Wordsworth’s “Tintern Abbey,” the article argues that Coleridge came to practise textual severance—publishing poems and their contexts separately, as if unrelated to each other, so that their origin in writing about which he was guilty and anxious—on political grounds and personal—was not apparent. How conscious this severance was is, at this distance, undecidable: what is clear is that some of the context returned in disguised form, as if publication served unwittingly as a refraction of material that Coleridge had repressed; as a result, the published text contained more than Coleridge explicitly declared and, perhaps, knew.